Critical Thinking Analysis of 13-14 Years Old Students on Lens Refraction Material - Tanti, Tanti; Darmaji, Darmaji; Astalini, Astalini; Kurniawan, Dwi Agus; Kartina, Lia (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
This research aims to analyze HOTS-based science learning in terms of students' critical thinking skills. This research was conducted at SMPN 22 Jambi City using a mixed research method with explanatory design analysis. Two instruments were made in this research: the description test questions as an instrument for quantitative approach and interviews for qualitative approach. The research subjects consisted of 58 of 13-14 years old students selected using quota sampling. The tested topic was the lens refraction which consisted of 10 questions. Five indicators were tested; namely, the ability to provide basic explanation, basic support, interference, advanced clarification, and strategy and tactics. After analyzing students' answers, the average score for providing basic explanation was 3.31, building basic supports was 3.59, inferencing was 3.26, providing advanced explanation was 3.88, and utilizing strategies and tactics was 3.41. Students’ HOTS was high with the average scores in the 40-60 interval. Therefore, students’ critical thinking skills were sufficient, which affected students’ HOTS in science learning.